A participação de professores do Núcleo Regional de Educação de Ponta Grossa na constituição do campo da educação química no Paraná: um olhar a partir de Bourdieu. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Chemical education in the state of Paraná has been configuring itself as a field and the agents acting in this social space contribute to the constitution of this field with the production of knowledge. In this sense, we determined as a problem for this research: how the participation of chemistry teachers from basic education of the Regional Center of Education of Ponta Grossa (NRE - PG) formed by the State University of Ponta Grossa (UEPG), in the field of Chemical Education (EQ) in the state of Paraná? In order for the research problem to be answered, we have as general objective: To analyze how the participation of chemistry teachers from the basic education of the NRE - PG in the field of EQ in the state of Paraná. And as specific objectives: to identify the cultural capital of chemistry teachers in basic education at NRE - PG; explain the trajectories of these teachers in the field of EQ; and, to relate the cultural capital and the strategies of the investigated teachers. For data collection, we carried out a search on the website of the Department of Education about teachers working in the teaching of chemistry and a survey of the Lattes curricula of teachers on the CNPq (National Council for Scientific and Technological Development) platform. The research has a qualitative approach and the analysis was carried out with 45 Lattes curricula of chemistry teachers in basic education, from the NRE - PG, and the total of chemistry teachers belonging to the NRE - PG is 87 teachers, but only 45 have CV registered on the Lattes platform. The following sets of teachers were considered in the research: a) without graduate studies and without scientific-academic production; b) with postgraduation and without scientific-academic production; c) Without a graduate degree and with scientific-academic production; d) Graduate and scientific-academic production. In this research, the trajectories of teachers were analyzed with a view to their productions and postgraduate courses. We verified that teachers have an institutionalized, objectified and incorporated cultural capital, and that this is directly related to the strategies they have to enter and/or remain in the field. We carried out a content analysis and highlighted as the main result that the participation of chemistry teachers in basic education occurs through the productions they carry out and the postgraduate courses, which they continue to carry out even after the stability achieved in their careers, indicating the concern in specialize and contribute to the dissemination of science through their research results.
Keywords: Educação Química; Professores de Química; Capital Cultural; Chemistry Education; Chemistry Teachers; Cultural Capital; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA